2014
DOI: 10.1007/s10897-014-9771-y
|View full text |Cite
|
Sign up to set email alerts
|

Public Awareness of Genetic Nondiscrimination Laws in Four States and Perceived Importance of Life Insurance Protections

Abstract: Genetic testing has grown dramatically in the past decade and is becoming an integral part of health care. Genetic nondiscrimination laws have been passed in many states, and the Genetic Information Nondiscrimination Act (GINA) was passed at the federal level in 2008. These laws generally protect individuals from discrimination by health insurers or employers based on genetic information, including test results. In 2010, Connecticut, Michigan, Ohio, and Oregon added four questions to their Behavioral Risk Fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
40
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 22 publications
5
40
0
Order By: Relevance
“…69 However, it does not prohibit the use of genetic test results by companies offering life insurance or long-term care policies, which might be able to use that information to deny coverage or raise premiums. 70 It is therefore important that genetic testing be offered in the context of appropriate genetic counseling, so that insurance and other risks are fully discussed beforehand and the family is provided an opportunity to acquire appropriate insurance coverage before testing. Cardiovascular practitioners should be aware that although guidelines for interpretation of genetic testing results exist, interpretations can vary among laboratories.…”
Section: Impact Of Genetic Test Resultsmentioning
confidence: 99%
“…69 However, it does not prohibit the use of genetic test results by companies offering life insurance or long-term care policies, which might be able to use that information to deny coverage or raise premiums. 70 It is therefore important that genetic testing be offered in the context of appropriate genetic counseling, so that insurance and other risks are fully discussed beforehand and the family is provided an opportunity to acquire appropriate insurance coverage before testing. Cardiovascular practitioners should be aware that although guidelines for interpretation of genetic testing results exist, interpretations can vary among laboratories.…”
Section: Impact Of Genetic Test Resultsmentioning
confidence: 99%
“…The outcome of these genetic tests could therefore affect the pricing or structure of insurance available to a patient found to have a genetic disease or abnormality. As this fear of genetic discrimination began to permeate society and leach into health policy and political agendas, legislation introducing some nondiscrimination provisions was included in the Health Insurance Portability and Accountability Act (HIPAA) of 1996 and the Genetic Information Nondiscrimination Act (GINA) of 2008 [7]. A handful of states in the United States also provide some additional protective provisions.…”
Section: Discussionmentioning
confidence: 99%
“…A 2010 study conducted by Parkman et al used questions added to the Behavioral Risk Factor Surveillance System (BRFSS) survey in four states to assess public knowledge regarding legal protections from genetic discrimination. 1 Only 13.3% – 19.1% of respondents indicated that they were aware of laws (such as the Genetic Information Nondiscrimination Act, GINA) that “prevent genetic test results from being used to determine health insurance coverage and costs”. 1 In 2009, Laedtke et al sent surveys to 1500 members of the American Academy of Family Physicians assessing their knowledge of GINA and their concerns regarding genetic discrimination.…”
Section: Introductionmentioning
confidence: 99%
“…1 Only 13.3% – 19.1% of respondents indicated that they were aware of laws (such as the Genetic Information Nondiscrimination Act, GINA) that “prevent genetic test results from being used to determine health insurance coverage and costs”. 1 In 2009, Laedtke et al sent surveys to 1500 members of the American Academy of Family Physicians assessing their knowledge of GINA and their concerns regarding genetic discrimination. 2 Of the 401 physicians who responded, over half (54.5%) were not aware of GINA and 44% were “highly concerned” about their patients’ potential risk for genetic discrimination in health insurance.…”
Section: Introductionmentioning
confidence: 99%